(untitled) (Revista Archai, 2023)
Thinking as described in Plato’s Sophist undergoes two basic changes: it progresses by shifting from one to many and it regresses by shifting from many to one. The change from one to many is generative; the change from many to one is reductive. These opposing changes provide a tension for thinking, and like Heraclitus’ bow string, this tension gives thinking its efficacy. Thinking would wander and accumulate endlessly unless it regresses from many to one. Yet, thinking would stagnate if it could not progress from one to many. Both changes are essential characteristics of thinking, and both rest on memory. Memory constitutes the foundation of thought.